Prevalence of hypertension and its modifiable risk factors among rural population aged ≥13 years - Singh, S. P.; Chauhan, Chitra Rani; Verma, Vijayshree (International Journal Of Community Medicine And Public Health, 2020)
Background: Hypertension is a silent physiological ailment leading to bizarre pathological complications. Every year, some 12 million fatal and 20 million nonfatal strokes and myocardial infarctions occur worldwide (WHO, 2002). Prevalence was noted between rural and urban parts of India 27.6% (23.2-32.0) and 33.8% (29.7-37.8). Methods: Study design community-based cross-sectional study. Sampling technique multistage random sampling technique was used to select representative sample from rural population of Kanpur. Results: The overall prevalence of hypertension (HTN) in our study was found to be 21.27%, more among females 23.2% than males 19.7%. The results of logistic regression analysis with HTN status as dependent variable, to identify the effects of 6 risk factors (independent variables) for hypertension body mass index (BMI), grade of work, excess salt consumption, mental stress, smoking/chewing tobacco, alcohol intake. The odds ratio was 3.57 for the BMI with lower limit of 95% C.I. being 2.73, implying that it’s at least 2.73 times related to hypertension and odds of other risk factors shows that all the 6 risk factors related statistically. There was significant correlation was found between BMI, blood pressure (BP) and age. There was signiﬁcance (p<0.01) of positive correlation BMI with both systolic and diastolic BP with correlation coefficient (0.395) was stronger than diastolic BP (0.301). Conclusions: Overall prevalence of hypertension was 21.3%. Smoking, tobacco chewing increases the prevalence and Quantity of alcohol consumption were seemed to pose definite impact on mean systolic BP. BP levels increases steadily with increasing BMI and with decreasing level of physical activity (sedentary lifestyle).